CHARACTERISTICS OF PLACENTA PREVIA AT PROF. DR. I.G.N.G. NGOERAH CENTRAL GENERAL HOSPITAL IN 2022-2023 - Yunus, Yovilia Tio; Surya, I Gede Ngurah Harry Wijaya; Mahendra, I Nyoman Bayu; Budiana, I Nyoman Gede (E-Jurnal Medika Udayana; Vol 14 No 4 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i4.P17, 2025)
Placenta previa can cause the mother to experience bleeding with all its complications so it can lead to maternal death if not handled optimally. Hence, serious attention needs to be given to this matter. This study aims to determine the characteristics of placenta previa at Prof. Dr. I.G.N.G. Ngoerah Hospital in 2022-2023 based on maternal age, number of parity, pregnancy interval, cesarean section surgery history, curettage history, placenta accreta history, endometriosis history, and uterine myoma history. This study uses a descriptive method of cross sectional and uses a total sampling technique. The subjects of the study were all pregnant women with placenta previa at Prof. Dr. I.G.N.G. Ngoerah Hospital Denpasar. This research data is secondary data obtained from medical records at Prof. Dr. I.G.N.G. Ngoerah Hospital Denpasar from January 1, 2022 to December 31, 2023. The collected data is processed, and presented in the form of tables and narratives. In this study, the number of samples that met the inclusion and exclusion criteria was 38 samples. The highest percentage of cases was found in the age of 21-34 years (65.8%). Most of them belonged to the multipara group (50.0%), had a pregnancy gap of > 2 years (60.5%), and had a history of cesarean section surgery (73.7%). In addition, more cases had no history of curettage (73.7%), no history of placenta accreta (65.8%), no history of endometriosis (97.4%), and no history of uterine myoma (92.1%). Based on the results of the study, it can be concluded that the characteristics of placenta previa at Prof. Dr. I.G.N.G. Ngoerah Hospital in 2022-2023 are at most 21-34 years old, multipara, have a pregnancy interval of > 2 years, have a history of cesarean section surgery, no history of curettage, no history of placenta accreta, no history of endometriosis, and no history of uterine myoma. Keywords : Placenta previa, pregnant women, Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital